2022
DOI: 10.1038/s41598-022-21426-7
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of the test design and performance of AI/ML-based medical devices approved for triage/detection/diagnosis in the USA and Japan

Abstract: The development of computer-aided detection (CAD) using artificial intelligence (AI) and machine learning (ML) is rapidly evolving. Submission of AI/ML-based CAD devices for regulatory approval requires information about clinical trial design and performance criteria, but the requirements vary between countries. This study compares the requirements for AI/ML-based CAD devices approved by the US Food and Drug Administration (FDA) and the Pharmaceuticals and Medical Devices Agency (PMDA) in Japan. A list of 45 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…AI research in radiology is an active field in healthcare owing to its affinity for imaging [ 14 ], with the number of AI-related publications and medical device certifications increasing annually [ 15 17 ]. One important reason for this is the global shortage of radiologists [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…AI research in radiology is an active field in healthcare owing to its affinity for imaging [ 14 ], with the number of AI-related publications and medical device certifications increasing annually [ 15 17 ]. One important reason for this is the global shortage of radiologists [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence algorithms can assist human clinicians in various medical fields 4 , 5 . Among the artificial intelligence algorithms, the reinforcement learning algorithms can find the optimal policy by maximizing the cumulative expected reward 6 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on the systematic analysis to clarify the test design of AI/ML-based CAD at pre-market demonstrated that CAST was approved based on SA, whereas CADe and CADx were approved based on RT in the U.S. [14] However, no studies have been conducted to determine how post-market improvement should be evaluated. Therefore, the lack of predictability of whether post-market improvements should be evaluated using SA or RT is an obstacle for start-ups and other companies developing medical devices based on AI technology.…”
Section: Introductionmentioning
confidence: 99%